2018
DOI: 10.3855/jidc.9886
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of different storage conditions for Staphylococcus hyicus survival

Abstract: Introduction: Collecting swabs from skin lesions for bacteriological examination is frequently performed to the diagnosis of exudative epidermitis. This method is fast and non-invasive, but it depends directly on the viability of bacteria in clinical samples, which can be influenced by storage and shipment temperatures and the time of transportation. The aim of this study was to assess the capacity of four commercial transport media and swabs with no transport medium to preserve Staphylococcus hyicus (S. hyicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…On the contrary to our findings, the addition of a transport medium, such as Amies or Stuart medium, has been shown to better preserve bacterial species by inactivating toxic substances or by keeping the swab fibres moist during transport to the laboratory (Barber et al, 1998; Barry et al, 1972; Drake et al, 2005). Some other studies reported the performance of Amies with‐ or without‐charcoal and Stuart media are likely to be confounded by storage temperature and time (Cumming & Ross, 1979; Takeuti et al, 2018). To the authors' knowledge, the present study is the first to demonstrate the differences in specimen type in the recovery of R. salmoninarum using bacterial culture.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary to our findings, the addition of a transport medium, such as Amies or Stuart medium, has been shown to better preserve bacterial species by inactivating toxic substances or by keeping the swab fibres moist during transport to the laboratory (Barber et al, 1998; Barry et al, 1972; Drake et al, 2005). Some other studies reported the performance of Amies with‐ or without‐charcoal and Stuart media are likely to be confounded by storage temperature and time (Cumming & Ross, 1979; Takeuti et al, 2018). To the authors' knowledge, the present study is the first to demonstrate the differences in specimen type in the recovery of R. salmoninarum using bacterial culture.…”
Section: Discussionmentioning
confidence: 99%
“…Забір мазків з уражень шкіри для бактеріологічного дослідження проводять з застосуванням транспортного середовища Еймса в охолодженому стані (Takeuti et al, 2018).…”
Section: рис 1 загальний вигляд добових колоній Staphylococcus Hyicus...unclassified